Type 2 Diabetes Mellitus and Associated Major Risk Factors - Khalil Mobin, Riaz Khanzada, Shakeel Ahmed, Farooq Memon, Hina Naz, Abdul Samad, Shehla Naseem, Mohammad Zaman Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine association of T2DM with depression, Covid-19, hypertension, junk food, weight, age, physical activity, smoking, family history, education and income. Study Design: Cross-sectional, multicenter study Duration and Place of Study: Family Health Clinic, Mehmoodabad, Ahmad Medical Centre, FB Area Karachi, Al-khidmat Hospital North Karachi, Rafah-E-Aam Hospital FB Area Karachi, from 1st November 2020 to 30th April 2021. Methodology: Pre-tested, researcher administered questionnaire was used through medics and paramedics. Information was collected from general patients and care givers. Non–diabetics and non-hypertensives were tested/checked on the spot. Results: Mean age of the participants was 35 years with minimum 18 and maximum 70 years. Males were 279 (95%). In males 30 (11%) were diabetic and in females 7 (47%) were diabetic. 168 (57%) of the participants got above matric education. Low-income group consisted of 271 (92%) participants. Diabetes was present in 37 (13%). Forty six percent diabetics were diagnosed incidentally. Most (24; 65%) were diagnosed by general practitioner, six (16%) by Family Physician, four (11%) by specialist and one (3%) by self. Conclusions: General practitioners play a pivotal role in diagnosing and managing diabetes mellitus. To reduce the burden of diabetes in Pakistan, modifiable risk factors like low education and high inflation have to be addressed. More over marriages between first cousins need to be discouraged. Keywords: Diabetes mellitus, Junk food, Lifestyle, Obesity